2022
DOI: 10.1021/acsaelm.2c00688
|View full text |Cite
|
Sign up to set email alerts
|

Ethylenediaminetetraacetic Acid (EDTA) Assisted Single Step Densification of Li2TiO3/PTFE Composites at Ultralow Sintering Temperature to Realize a High-Performance Ku-Band Antenna

Abstract: In the last few decades, extensive research has been focused on the ever-increasing demand for energy-efficient materials and technologies in consumer electronics. The low-weight, low-cost, environmentally safe Li-based ceramics are widely investigated as potential materials for Li-ion batteries and low-temperature cofired ceramics (LTCC). In the present work, we combine high volume fractions of Li2TiO3 (LT) ceramic with incredibly versatile polytetrafluoroethylene (PTFE) to synthesize thermally stable, low-lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 74 publications
(151 reference statements)
0
4
0
Order By: Relevance
“…The resonant frequencies of simulated and fabricated MPAs are 5.20 and 5.29 GHz, respectively. Basically, return loss indicates the power reflected from the antenna to the source, and it should be less than −10 dB for the entire acceptable frequency range. , Here, the simulated and fabricated antennas show return loss values of around −20.2 and −17.9 dB, respectively, which are good enough for their practical application. Another parameter that determines the suitability of the antenna for a specific application is its impedance bandwidth, which corresponds to the range of frequencies where the return loss is less than −10 dB.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…The resonant frequencies of simulated and fabricated MPAs are 5.20 and 5.29 GHz, respectively. Basically, return loss indicates the power reflected from the antenna to the source, and it should be less than −10 dB for the entire acceptable frequency range. , Here, the simulated and fabricated antennas show return loss values of around −20.2 and −17.9 dB, respectively, which are good enough for their practical application. Another parameter that determines the suitability of the antenna for a specific application is its impedance bandwidth, which corresponds to the range of frequencies where the return loss is less than −10 dB.…”
Section: Resultsmentioning
confidence: 80%
“…35 Also, recently, Santha et al used EDTA as the sintering aid to densify the Li 2 TiO 3 -PTFE composites. 36 In the recent past, on account of the lower polarizability of F − (1.62 Å 3 ) than that of an O 2− ion (2.01 Å 3 ), researchers have more focused on fluoride-based systems to take advantage of CSP for promising microwave dielectric ceramics. Liu et al demonstrated the feasibility of the cold sintering technique followed by the annealing process on the densification of LiF ceramics.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Li 2 TiO 3 -based materials have shown promise in high-frequency resonant circuits. It has a dielectric constant (ε r ) of around 26 and can be sintered at relatively low temperatures, such as 900 • C [25]. Therefore, they are suitable for lowtemperature processing applications.…”
Section: 5mentioning
confidence: 99%